Anion sensing in aqueous media by photo-active transition-metal bipyridyl rotaxanes. - Hancock, L; Marchi, E; Ceroni, P; Beer, P (2012)
A chloride anion templation methodology is utilized in the construction of novel transition-metal rhenium(I) and ruthenium(II) bipyridyl appended [2]rotaxanes. (1)H NMR spectroscopic titrations reveal the ability of the rotaxanes to selectively bind chloride over the more basic oxoanions, with the ruthenium(II) bipyridyl appended rotaxane strongly binding chloride in 30% water. Photophysical investigations demonstrate the ability of the rotaxanes to sense anions in aqueous media, with chloride being selectively complexed, in general agreement with NMR spectroscopy determined anion binding data.